Designing Sample of Teaching Reading Recount Text Module by using Experience-Text-Relationship (ETR) for Lower Secondary Students - Novia Elma Ashariana; Rahayu Apriliaswati; Wardah Wardah (FKIP, Universitas Palangka Raya, 2025)
This research was aimed at providing a media for teaching reading recount text of eighth-grade students by using the Experience-Text-Relationship (ETR) method. This research was categorized as research and development. This research used three phases of ADDIE, namely Analyze, Design, and Develop. First, this research aims to analyze the 2013 Curriculum, the students’ needs, and the appropriate materials. Second, the research aims to design modules with the Experience-Text-Relationship (ETR) method that can enhance the students’ reading ability. Third, this research is to develop the prototype, especially material design. The tool of data collecting is an interview sheet for English teacher, it used to be the data of students’ problems in class. Data analysis used descriptive qualitative analysis. This research provided results that students and teachers need modules that are able to improve reading skills in teaching-learning. This research concludes that the designing example of teaching reading recount text by using the Experience-Text-Relationship (ETR) method to increases students’ reading skills, allow the students to attempt to achieve reading goals, and increases their interest in studying English.